An application of Delphi method and analytic hierarchy process in understanding hotel corporate social responsibility performance scale. Issue 7 (12th April 2021) - Wong, Antony King Fung; Kim, Seongseop (Sam); Lee, Suna; Elliot, Statia
Abstract: This study aims to identify the essential indicators of hotel Corporate Social Responsibility (CSR) performance measurement with a standardized and composite CSR performance measurement index for the hotel industry. Employing both Delphi and Analytic Hierarchy Process (AHP) methods, three stakeholder groups are surveyed: academicians; hotel managers; and, hotel customers. Results reveal that three traditional CSR domains (legal, ethical, and social/philanthropic) are primary contributors to CSR performance, followed by two new environmental domains (room and restaurant; other general areas), and financial/economic domains as secondary contributors. This study shows the high level of consistency in the responses from stakeholder groups, supporting the effectiveness of the scale as a valuable tool to measure hotel CSR performance. Notably, domain weighted scores do differ slightly by respondent characteristic, indicating that the impacts of CSR are sensitive to respondent diversity.